Fluorescent mannosides serve as acceptor substrates for glycosyltransferase and sugar-1-phosphate transferase activities in Euglena gracilis membranes. (13th January 2017) - Ivanova, Irina M.; Nepogodiev, Sergey A.; Saalbach, Gerhard; O'Neill, Ellis C.; Urbaniak, Michael D.; Ferguson, Michael A.J.; Gurcha, Sudagar S.; Besra, Gurdyal S.; Field, Robert A.
Abstract: Synthetic hexynyl α-D-mannopyranoside and its α-1, 6-linked disaccharide counterpart were fluorescently labelled through CuAAC click chemistry with 3-azido-7-hydroxycoumarin. The resulting triazolyl-coumarin adducts, which were amenable to analysis by TLC, HPLC and mass spectrometry, proved to be acceptor substrates for α-1, 6-ManT activities in mycobacterial membranes, as well as α- and β-GalT activities in trypanosomal membranes, benchmarking the potential of the fluorescent acceptor approach against earlier radiochemical assays. Following on to explore the glycobiology of the benign protozoan alga Euglena gracilis, α-1, 3- and α-1, 2-ManT activities were detected in membrane preparations, along with GlcT, Glc-P-T and GlcNAc-P-T activities. These studies serve to demonstrate the potential of readily accessible fluorescent glycans as substrates for exploring carbohydrate active enzymes. Graphical abstract: Highlights: Assays for the analysis of carbohydrate-active enzymes that rely upon fluorescent acceptor substrates are set out. New assays are validated by benchmarking against radiochemical work with known glycosyltransferase activities. The installation of a fluorophore on acceptor substrates was easily achieved through click chemistry. Fluorescence assays are used to discover GTs activities in Euglena gracilis microsomal membranes.